Pemetaan Daerah Reseptif Vektor Malaria di Kabupaten Kulon Progo : Mapping Malaria Vektor Receptive Areas in Kulon Progo Regency - Elia, Tasya; Astuti, Fardhiasih Dwi; Sukamto, Ali (Aspirator, 2024)
Malaria is a re-emerging disease. According to the Ministry of Health, malaria cases in Indonesia are second only after India in Southeast Asia. The Special Region of Yogyakarta is one of the cities with the most malaria endemic, precisely in Kulon Progo Regency. Malaria cases in Kulon Progo Regency are experiencing fluency. Kulon Progo Regency itself received a malaria elimination certificate in 2022. Maintenance of malaria elimination can be done by knowing the mapping of malaria vector receptive areas. This study aims to determine the type of Anopheles mosquito larval habitat, determine the coordinates of Anopheles mosquito larval habitat, determine the Anopheles mosquito larval habitat index, and determine the mapping of malaria vector receptive areas in Kulon Progo Regency. The quantitative descriptive research method used spatial analysis with malaria vector receptive areas mapping in Kulon Progo Regency. Inclusion criteria were villages surveyed for malaria mosquito larvae in the mosquito vector survey activities carried out by the Kulon Progo Regency Health Office and Puskesmas in Kulon Progo Regency in 2023. The habitats found in Kulon Progo Regency are rivers, neighborhoods around houses, irrigation, ponds, rice fields, and lagoons, with the most positive habitats in rivers at 35%. Coordinate points are drawn according to the type of habitat found. The highest Anopheles mosquito larval habitat index in Kulon Progo Regency is Kalirejo Village, with a habitat index of 74%, and there are 19 malaria vector receptive villages based on the Anopheles mosquito larval habitat index. The mapping of receptive areas can be used as a reference formalaria prevention and control efforts in the Kulon Progo Regency.